DRUG RELATED PROBLEMS ON CHILDREN IN-PATIENTS WITH LOWER RESPIRATORY TRACT INFECTION AND ASTHMA IN PANTI RAPIH HOSPITAL YOGYAKARTA ON 1ST JANUARY – 30TH JUNE 2006 - Dyah Anggraeni Budhi Pratiwi; Zullies Ikawati; Wara Kusharwanti (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Drug related problems commonly happen to children. The treatment of these problems should be prioritizedbecause their physiologic factor have not perfect yet, so the drugs metabolism and absorption are different. Lowerrespiratory tract infection and astma were causes of children’s pain, and its also still become major problem in medicalfield. This research was generally aimed for investigating drug related problems happened to children with lower respiratory infection in Panti Rapih Hospital Yogyakarta on January until June 2006.This was a non-experiment research conducted in descriptive concept through retrospective data collecting from the medical record of children with lower respiratory tract infection and astma treated in Panti Rapih Hospital Yogyakarta on January until June 2006. These problems were analyzed from the medical record of the patients andthen analized percentage of drug related problems.There were 77 patients who fit the inclusion criteria in this research, number of children in patients with lowerrespiratory tract infection was 55 patients and 22 patients for asthma. The result of research to children in patients with lower respiratory tract infection showed that unnecessary drug therapy was 20%, Wrong drug was 12.72%,too low dosage was 7.27%, too high dosage was 21.81%, and drug interactions was 12.72%. The result of research tochildren in patients with asthma showed that unnecessary drug therapy was 18.18%, wrong drug was 4.54%, dosagetoo high was 13.63%, Drug interactions was 50% and uncompliance was 4.54%. Key words: Drug Related Problems, Lower Respiratory Tract Infection, Pediatric